Phase-transition induced optimization on electrostrain, electrocaloric refrigeration and energy storage of LiNbO3 doped BNT-BT ceramics - Zhang, Yueming; Liang, Guochuang; Tang, Silin; Peng, Biaolin; Zhang, Qi; Liu, Laijun; Wenhong, Sun (Elsevier, 2019)
((Bi0.5Na0.5TiO3)0.88-(BaTiO3)0.12)(1-x)-(LiNbO3)x (x = 0.0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, and 0.07; abbreviated as LiNbO3-doped BNT-BT) ceramics possessing many excellent performances (large electrostrain, negative electrocaloric effect and energy storage density with high efficiency) was fabricated by the conventional solid-state reaction method. A large electrostrain (maximum ~ 0.34% at 100 kV/cm and room temperature) with high thermal stability over a broad temperature range (~80 K) is obtained at x = 0.03. A large energy storage density (maximum Wenergy ~ 0.665 J/cm3 at 100 kV/cm and room temperature) with a high efficiency (η ~ 49.3%) is achieved at x = 0.06. Moreover, a large negative electrocaloric (EC) effect (maximum ΔT ~ 1.71 K with ΔS ~ - 0.22 J/(K kg) at 70 kV/cm)) is also obtained at x = 0.04. Phase transition (from ferroelectric to antiferroelectric and then to relaxor) induced by increasing the doping amount of LiNbO3 plays a very key role on the optimization of these performances. These findings and breakthroughs make the LiNbO3-doped BNT-BT ceramics very promising candidates as multifunctional materials.
Keywords: Phase-transition; Electrostrain; Energy storage; Electrocaloric effect